HUBUNGAN PENGETAHUAN IBU TENTANG MAKANAN PENDAMPING ASI (MP-ASI) DENGAN KEJADIAN DIARE PADA BAYI USIA 6-12 BULAN DI RW 06 TANGGULANGIN SIDOARJO - Erika Untari Dewi (Bahasa Indonesia, 2020)
Side dish of ASI is passed to food baby / child beside ASI to fulfill its requirement of him. MP-ASI start to be passed to age 6-24 months and represent switchover food of ASI family food. Occurence of diarrhoea Most hit by child isdiarrhoea have this 6-12 months age to represent child moments learn to eat other food and beverage beside irrigate mother milk. Meanwhile eaten by food is child possible contain many this germ cause intestine infection and child hit by diarrhoea. Diarrhoea caused by change at child food of mother milk water to child food start discipline. Target of this research to know Relation Knowledge Of Mother About Food of Pendamping ASI (MP-ASI) With Occurence Of Diarrhoea At Baby Age 6-12 Months in RW 06TanggulanginSidoarjo. Desain which [is] used in this research descriptive research. takenSampel counted 20 responder fulfilling criterion of inklusi. Sampling the used istotalizeing sampling. Pursuant to result of research which have can be concluded that timgkat knowledge of knowledgeable mother less counted 12 people that is ( 60%). Pursuant to result of research which have can be concluded that occurence of Diarrhoea Baby Age 6-12 Months in RW 06TanggulanginSidoarjoisoccurence have never 10 people (50%). Pursuant to result of research which have can be concluded that [Relation/Link] Knowledge Of Mother About Food of Pendamping ASI (MP-ASI) With Occurence Of Diarrhoea At Baby Age 6-12 Months in RW 06Tanggulangin Sidoarjo is there no relation